اختصاص القاضي الإداري بمنازعات سلطات الضبط المستقلة - قشاب ،الجموعي; غندير، العايش; بكاري، حــــــــده (جامعة الوادي University of El Oued, 2024)
تمثل السلطات الإدارية المستقلة جهات إدارية جديدة منحها المشرع تنظيم مجموعة من القطاعات، سواءً في الجانب المالي أو الاقتصادي أو الإعلامي، حيث أسند لها مجموعة من الاختصاصات هي في الأصل كانت حكراً على السلطة التنفيذية، وهذا نتيجة تحول دور الدولة من خلال التغيرات التي شهدتها المنظومة العامة للدولة، وتتمتع هذه السلطات باستقلالية في تسيير شؤونها الإدارية، حيث يتمتع بعضها بالاستقلال المالي والشخصية المعنوية، إلا أن المشرع أخضع منازعاتها لرقابة القاضي الإداري وذلك حرصا منه على تحقيق مبدأ المشروعية باعتبارها هيئات عمومية وطنية، وحتى لا تحيد عن الدور الذي أنشأت من أجله، حيث تبين لنا من خلال هذه الدراسة عدم توحيد القواعد العامة التي تحكم منازعات هذه السلطات، حيث تطبق أحيانا قواعد إجرائية حسب ما نصت عليه النصوص المنشئة لها، وفي حالة عدم وجود هذه النصوص يلجأ القاضي الإداري للقواعد العامة، ومن هنا نكون أمام اختلاف وتباين في تحديد الإجراءات والمواعيد، وكذا في تطبيق قواعد الاختصاص بين القانون الخاص والقانون العام. The Independent administrative authorities représente new administrative bodies granted by the legislator to regulate a group of sectors, whether in the financial, economic, or media aspect, as they were assigned a set of competencies that were originally exclusive to the executive authority. This is the result of the transformation of the role of the state through the changes witnessed by the public system. To the state. These authorities enjoy independence in managing their administrative affairs, as some of them enjoy financial independence and moral personality. However, the legislator has subjected their disputes to the supervision of the administrative judge in order to achieve the principle of legality as national public bodies, and so that they do not deviate from the role for which they were established. Through this study, we found that the general rules governing disputes between these authorities are not unified, as procedural rules are sometimes applied according to what was stipulated in the texts establishing them. In the absence of these texts, the administrative judge resorts to general rules, and from here we are faced with disagreement and variation in determining Procedures and deadlines, as well as in applying the rules of jurisdiction between private law and public law
ماستر اداري